(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Using ChatGPT regularly produces academic success, plus it develops moral critical thinking abilities and problem-solving capabilities. The use of ChatGPT creates ongoing concerns for stakeholders regarding system dependency and ethical implications that surface when users implement it. However, stakeholders continue to raise multiple concerns about both dependence on ChatGPT and the moral ramifications that come from using it. This study aims to analyze the impact of generative AI, particularly ChatGPT, on the academic performance of undergraduate students in five federal leading universities in Nigeria. A statistical analysis using Chi-square tests together with independent t-tests discovered meaningful relationships connecting academic achievements to ChatGPT usage. The study reveals that educational institutions can achieve effective results when combining AI tools like ChatGPT with conventional methods under strategic circumstances and need continuous ethical monitoring. Academic liability and the sustained advancement of critical thinking competence remain unharmed when ChatGPT use is implemented correctly.